Whey protein gel composites in the diet of goats increased the omega‐3 and omega‐6 content of milk fat. Issue 4 (6th August 2015) - Weinstein, J. A.; Taylor, S. J.; Rosenberg, M.; DePeters, E. J.
Summary: Previously, feeding whey protein gels containing polyunsaturated fatty acids (PUFA) reduced their rumen biohydrogenation and increased their concentration in milk fat of Holstein cows. Our objective was to test the efficacy of whey protein isolate (WPI) gels produced in a steam tunnel as a method to alter the fatty acid (FA) composition of the milk lipids. Four primiparous Lamancha goats in midlactation were fed three diets in a 3 × 4 Latin square design. The WPI gels were added to a basal concentrate mix that contained one of three lipid sources: (i) 100% soya bean oil (S) to create (WPI/S), (ii) a 1:1 (wt/wt) mixture of S and linseed (L) oil to create (WPI/SL), or (iii) 100% L to create (WPI/L). Periods were 22 days with the first 10 days used as an adjustment phase followed by a 12‐day experimental phase. During the adjustment phase, all goats received a rumen available source of lipid, yellow grease, to provide a baseline for milk FA composition. During the experimental phase, each goat received its assigned WPI. Milk FA concentration of C18:2 n‐6 and C18:3 n‐3 reached 9.3 and 1.64 g/100 g FA, respectively, when goats were fed WPI/S. Feeding WPI/SL increased the C18:2 n‐6 and C18:3 n‐3 concentration to 6.22 and 4.36 g/100 g FA, and WPI/L increased C18:2 n‐6 and C18:3 n‐3 to 3.96 and 6.13 g/100 g FA respectively. The adjusted transfer efficiency (%) of C18:3 n‐3 to milk FA decreased significantly as dietary C18:3 n‐3 intake increased. Adjusted transfer efficiency for C18:2 n‐6 did not change with increasing intake of C18:2 n‐6. The WPI gels were effective at reducing rumen biohydrogenation of PUFA; however, we observed a change in the proportion increase of C18:3 n‐3 in milk FA suggesting possible regulation of n‐3 FA to the lactating caprine mammary gland.